Handbook of RF and microwave power amplifiers - Walker, John L. B. (Cambridge RF and microwave engineering series., 2012)
"Whether you are an RF transistor designer, an amplifier designer or a system designer, this is your one-stop guide to RF and microwave transistor power amplifiers. A team of expert authors brings you up to speed on every topic, including: devices (Si LDMOS and VDMOS, GaAs FETs, GaN HEMTs), circuit and amplifier design (discrete, hybrid and monolithic), CAD, thermal design, reliability, and system applications/requirements for RF and microwave transistor amplifiers. Covering state-of-the-art developments and emphasising practical communications applications, this is the complete professional reference on the subject"--